Dampak Aktivitas Swalayan Grand Hero Terhadap Kinerja Ruas Jalan Basuki Rahmat di Kota Palu - Kasan, Muhammad; Tahir, Anas; Usman, Usman (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2015)
One of the few supermakets in Palu city which considerably crowded is Grand Hero Supermarket. This Supermarket was located on the Basuki Rahmat street. Because this road is an arterial road with highly traffic volume at certain hours, so the Grand Hero Supermarket activity will affect the performance of the road. At peak hours, many vehicles are in and out from the supermaket, disrupting theperformance of BasukiRahmat road. The aim of this research is to understand the existing condition of the Basuki Rahmat street performance with or without the activity of Grand Hero Supermaket. This research was conducted by surveying the volume of the street, side friction and travel time. The survey was carried on Wednesday 04-06-2015 and Saturday 6-06 2015. The analysis was conducted by using Manual Kapasitas Jalan Indonesia 1997 method. The results show that the performance of JalanBasuki Rahmat with no Grand Hero Supermarketâ€™s activity has a degree of saturation 0.35. Grand Hero Supermarket with activity would increase the degree of saturation that is 0.43 that increases 22.86%. The speed of light vehicles by MKJI isÂ  42.84 km / h. With the Grand Hero Supermarket activity, the speed of light vehicle decreased from 27.76 km/ h to 23.74 km / h or there are speed reductions of 14.49%. The level of service with the Grand Hero Supermarket activity was at B condition with DS rate of 0,43